Associations between urea nitrogen and risk of depression among subjects with and without type 2 diabetes: A nationwide population-based study - Mao, Yafei; Li, Xinyuan; Zhu, Shumin; Ma, Jin; Geng, Yulan; Zhao, Yuanyuan (Frontiers in Endocrinology, 2022)
(1) Background: Depression and type 2 diabetes (T2D) are serious public health problems with irreversible health consequences and a significant economic burden on the healthcare system. Previous studies have suggested that blood urea nitrogen (BUN) was inversely longitudinally associated with incidence of diabetes and depression in adults, but few well-designed studies have examined the effects of status of T2D on the full range of relationship between BUN and depression. (2) Methods: The analysis sample consisted of adults aged≥20 years from the 2007-2014 National Health and Nutrition Examination Survey (NHANES) who completed the Patient Health Questionnaire-9 (PHQ–9), involving 19,005 participants. By stratifying participants according to T2D status, we further assessed the difference between BUN and risk of depression in participants with and without T2D using multivariate logistic regression (interaction test). (3) Results: In this cross-sectional study, the association between BUN and depression prevalence appeared to differ between the T2D and non-T2D groups (OR: 1.00, 95% Cl: 0.95-1.05 vs. OR: 0.89, 95% Cl: 0.85-0.93). In addition, there was evidence of an interaction between BUN levels and T2D status in reducing the risk of depression (P value for interaction = 0.032.) The relationship between BUN and depressive symptoms was significant in non-T2D subjects (P < 0.001), but not in T2D (P = 0.940). (4) Conclusions: Our findings suggest that there is a significant relationship between BUN and depression, and T2D status may influence the association between BUN and the risk of depression. Such findings require further prospective studies to provide more evidence.